Men users of LPG stoves have more frequency of respiratory symptoms than users of biomass fuel stoves at Ayacucho, Peru (2750 masl) - Phocco, Erick (2019)
ABSTRACT. Rationale: Peru has around 9 million of households. In 30% of them biomass fuel stoves is used to prepare meals. Respiratory diseases as chronic bronchitis, pneumonia, asthma are more frequent in people using traditional biomass stoves. Peruvian government has donated around 1500000 LPG stoves with its balloon and 5 dollars monthly subsidy tobuy LPG. In Peru there were around 450000 improved certified biomass stoves. More time near the pollutant biomass stoves spend women and children than men. Methods We studied men, from 9 rural communities at Ayacucho, Peru, (2750 masl). After signed the inform consent a history and clinical exam was realized. 57.9% (98) were users simultaneously of traditional and improved biomass stoves and 42.1% (71) were users of LPG stoves but simultaneously were using traditional and/or improved biomass stoves, ranging their ages between 19 and 89 years old. Statistical analysis was performed using STATA v. 13. Results Men users of only biomass stoves have lesser symptoms than those users simultaneously of LPG and biomass stoves: Phlegm (33.7% vs 50.7%, p = 0.020), phlegm when getting up in the morning (35.7% vs. 55.7%, p = 0.008), phlegm resting lying down (23.5% vs 36.6%, p = 0.046), phlegm for 3 consecutive months (16.3% vs. 28.6%, p = 0.044) and cough and phlegm in the last two years (28.6% vs 53.5%, p = 0.001).